Effect of Injection Pressure, Injection Duration, and Injection Frequency on Direct Injector’s Mass Flow Rate for Compressed Natural Gas Fuel - Mohamad Hafizul Rahman, Alias; Mohd Fadzil, Abdul Rahim; Muhamad Haziq, Mohd Ismail Rodzi; Rosli, Abu Bakar (EDP Sciences, 2018)
A conventional gasoline direct injector is converted for gaseous fuel application. The conversion alters the injector characteristic which further affect the mixture formation and combustion processes. The purpose of this study is to investigate the effects of injection pressure (case 1), injection duration (case 2), and injection frequency (case 3) on the injector’s mass flow rate. An injector was independently tested by using an injector test bench. In Case 1, the injection pressure was tested from 20 bar to 60 bar at 24 ms of injection duration for 1000 injection counts. In Case 2, the injection duration was set from 2 to 24 ms at a constant 50 bar injection pressure for different engine speed. Whereas in Case 3, the averaged mass flow rate are plotted at different injection frequency. Theoretical calculations were carried out to compare the experimental and theoretical result. The experiment results shown that the injection pressure affected the injector mass flow rate linearly. At short injection duration, the mass flow rate inconsistent and highly fluctuated. At higher injection frequency, the mass flow rate is becoming higher. The theoretical results able to predict the mass flow rate trend but were unable to spot the fluctuating effects.